Current chemotherapeutic options for the treatment of gestational trophoblastic disease. (22nd January 2023) - Braga, Antonio; Paiva, Gabriela; Cattai, Cassia Juliana; Elias, Kevin M.; Horowitz, Neil S.; Berkowitz, Ross S.
ABSTRACT: Introduction: Gestational trophoblastic neoplasia (GTN) is a rare tumor that arises from trophoblastic tissues with high remission rates after chemotherapy treatment. GTN can develop from any gestational events, such as miscarriage, ectopic pregnancy, and preterm/term pregnancy, but is more frequent after hydatidiform mole. The sensitivity of this tumor to chemotherapy and the presence of an exceptional tumor marker allow high remission rates, especially when patients are treated in referral centers. Areas covered: Observational, retrospective, prospective, systematic reviews, and meta-analysis studies focusing on GTN treatment. We searched PubMed, Medline, and the Library of Congress from January 1965 to May 2022. Expert opinion: Early GTN diagnosis allows low-toxic and highly effective treatment. Even multimetastatic disease has high rates of remission with multiagent regimen chemotherapy. Surgery is reserved for uterine disease in patients who have completed childbearing, in cases of chemoresistance to multiagent regimens or in the rare cases of placental site trophoblastic tumor or epithelioid trophoblastic tumor. While resistance is managed by salvage chemotherapy, cases with limited clinical response to sequential regimens have been successfully treated with immunotherapy.